Viral Hepatitis A, B and C in a Group of Transgender Women in Central Brazil - Lucila Pessuti Ferri; Priscilla dos Santos Junqueira; Mayara Maria Souza de Almeida; Mariana Gomes Oliveira; Brunna Rodrigues de Oliveira; Bruno Vinícius Diniz e Silva; Larissa Silva Magalhães; Lívia Melo Villar; Karlla Antonieta Amorim Caetano; Márcia Maria Souza; Megmar Aparecida dos Santos Carneiro; Regina Maria Bringel Martins; et al. (Tropical Medicine and Infectious Disease, 2022)
Transgender women (TGW) have limited access to affordable viral hepatitis testing, hepatitis B vaccination, and treatment. We aimed to estimate the prevalence of viral hepatitis A, B, and C, as well as to compare the adherence and immunogenicity of two hepatitis B vaccine schedules among TGW in Central Brazil. A total of 440 TGW were interviewed and tested for hepatitis A, B, and C serological markers from 2017 to 2018. The hepatitis B vaccine was offered to 230 eligible TGW: 112 received a super accelerated hepatitis B vaccine schedule (G1) and 118 a standard schedule (G2). The antibody against the hepatitis A virus (HAV) was detected in 75.63% of the participants, and 12.3% of the TGW were exposed to the hepatitis B virus (HBV). Two (0.46%) participants were HBV carriers. Only 41.5% of the participants showed a serological profile of hepatitis B vaccination. The antibody against the hepatitis C virus (anti-HCV) was found in six participants (1.37%). Of the TGW who received the first vaccine dose, 62 (55.36%) and 49 (41.52%) in G1 and G2, respectively, received three doses (p = 0.036). The vaccine response was evaluated in 28 G1 and 22 G2 TGW; of these, 89.3% and 100% developed protective anti-hepatitis B surface-antigen titers, respectively (p = 0.113). Since one-third of younger transgender women are susceptible to HAV, hepatitis B immunization is low, and the anti-HCV rate is higher in this group than in the general population in Central Brazil, public-health attention is warranted. The super-accelerated scheme demonstrated better adhesion and good immunogenicity, suggesting that it would be a more cost-effective solution.